(untitled) (Eurasian Journal of Philology Science and Education, 2019)
From the modern point of view the cognitive character of philosophical thoughts in the stories of the classic of the Kazakh literature M. Auezov is interpreted in a new way, theoretical analyses are carried out from the point of view of the national worldview in this article. The deep analysis of the main ideas raised in the great writer’s novels giving a picture of humanistic character , it outlines the interrelated teachings about the goodness of the great akyn Abay and the East genius Confucius. For this purpose, a review of the historical situation in the Kazakh society of the second half of the 19th century was prepared, thereby expanding the research scope of the topic. The features of the content, thematic and ideological nature of M. Auezov’s stories written in 1920 and 1930 are mutually identified and comprehensively analyzed. Besides, carrying out comparison of various psychological manifestations of inner world of characters of the feature stories of the great writer with the natural phenomena, has drawn special attention to the skill descriptions, by means of a comparative method. From the scientific point of view the vital character of philosophical thoughts of the writer’s stories based on traditional Kazakh philosophy of understanding of an essence of life is analyzed, and the necessity of aspiration to the realization of the humanistic idea by means of human qualities is revealed for it.